A comparative study of use of negative drain in lichenstein repair for large inguinal hernia repair - Aaudichya, Abhay Kumar; Vaishnani, Bhavesh; Juneja, Ilias; Rajyaguru, Ajay; Dandi, Pravin; Singh, Rahul (International Journal of Research in Medical Sciences, 2017)
Background: Recently, with more attention to patient outcomes, post-operative seroma has noted as complication after open inguinal hernia repair. The main aim of the study was to compare and correlate the therapeutic effectiveness of negative suction drain versus no drain in large inguinal hernia repair. Methods: The present study is a randomized study of 400 cases of inguinal hernias admitted in PDU Government Medical College and Hospital, Rajkot, during the study period of April 2012 to March 2015. The cases for the purpose of the study were selected on the basis of the random sampling method and after taking valid informed consent. Results: The drains were used in 120 of 280 open mesh repairs of inguinal hernias. The patients who had drains were older, had cardiovascular disease, higher ASA class, and received anticoagulant regimens more often, had indirect type hernia more often, more commonly had emergency operations, had complicated presentations such as incarceration and strangulation, therefore had resections more often, had local complication such as hematoma, had longer duration of operation. Conclusion: Drain is more commonly used in patient who had more dissection and longer duration of operation. Drain used in selected patients seems to not increase infection risk but associated with longer hospital stay.